Head in the clouds - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory, 2018)
Dory, nicknamed Rascal, has her first loose tooth, but her excitement turns to concern when imaginary evil robber Mrs. Gobble Gracker captures the tooth fairy.